Influence of physical and chemical soil properties on the adsorption of Escherichia coli in Mollisols and Alfisols of Argentina - Behrends Kraemer, Filipe (2013)
Fil: Behrends Kraemer, Filipe. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.